1982
DOI: 10.1104/pp.70.5.1449
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chitosan on Membrane Permeability of Suspension-Cultured Glycine max and Phaseolus vulgaris Cells

Abstract: Treatment of suspension-cultured Glycine max cv Harosoy 63 cells with soluble chitosan (20-500 micrograms per milliliter) increased membrane permeability as shown by leakage of electrolytes, protein, and UV absorbing material. Severe damage to the cell membrane by chitosan (100 and 500 ug/ml) was also indicated by reduced staining with fluorescein diacetate and the leakage of fluorescein from preloaded cells. Other basic polymers (poly-L-lysine, histone, DEAE-dextran, protamine sulfate, and glycol chitosan) al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
0
4

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(114 citation statements)
references
References 26 publications
4
106
0
4
Order By: Relevance
“…One of them is the ability of chitin and its derivatives to activate defence mechanisms of the host organisms by inducing the accumulation of chitinases and other pathogenesis-related proteins (El Ghaouth et al, 1992). Another one is leakage in the cell wall of bacteria due to the interaction between positively charged chitin molecules and the negatively charged surface of the bacteria (Young et al, 1982). In Sparus aurata, Esteban et al (2001) observed an increase in the activity of innate immune system when chitin was incorporated in the diet.…”
Section: Discussionmentioning
confidence: 99%
“…One of them is the ability of chitin and its derivatives to activate defence mechanisms of the host organisms by inducing the accumulation of chitinases and other pathogenesis-related proteins (El Ghaouth et al, 1992). Another one is leakage in the cell wall of bacteria due to the interaction between positively charged chitin molecules and the negatively charged surface of the bacteria (Young et al, 1982). In Sparus aurata, Esteban et al (2001) observed an increase in the activity of innate immune system when chitin was incorporated in the diet.…”
Section: Discussionmentioning
confidence: 99%
“…Early research describing the antimicrobial potential of chitin, chitosan, and their derivatives dated from the 1980-1990s [9][10][11][12][13][14] . Generally, in these studies the chitosan is considered to be a bacteriocidal (kills the live bacteria or some fraction therein) or bacteriostatic (hinders the growth of bacteria but does not imply whether or not bacteria are killed), often with no distinction between activities.…”
Section: The Antimicrobial Models Of Chitosanmentioning
confidence: 99%
“…Antimikrobiyal özelliğinin yanı sıra kitosan gıda sanayinde elma suyu [85] ve sirke [86] üretiminde berraklaştırma maddesi, sosis üretiminde antioksidan [6], liçi [87], elma ve armut suyu [88] ile patateste [89] enzimatik esmerleşmeyi önleyici madde ve meyve sularında asitlik giderici ajan [90] olarak da kullanılmaktadır. Ayrıca kitosan su bağlama ajanı olarak da rol oynayarak birçok enzimi inhibe edebilmektedir [91]. Bilindiği üzere gıdalar farklı bileşiklerin (karbonhidrat, protein, yağ, mineral, vitamin vb.)…”
Section: Ki̇tosanin Gida Endüstri̇si̇ndeki̇ Uygulamalariunclassified